Socio-demographic characteristics, psychological factors and knowledge related to electric car use: A comparison between electric and conventional car drivers. (December 2018) - Simsekoglu, Özlem
Abstract: Increasing number of drivers are using electric cars either as their main or additional car. It is important to make a distinction between sole electric car drivers and drivers of both an electric and a conventional car to understand whether determinants of electric car use differ across these sub-groups. The main aim of the present study was to make comparisons among owners of sole electric car, both electric and conventional cars, and sole conventional car for demographic characteristics, travel mode use, psychological factors and knowledge related to electric car use in a Norwegian sample of car drivers. In addition, factors that predict type of car/s (electric, conventional or both electric and conventional) owned by the drivers were investigated. An online survey, with a response rate of 11%, was used to collect data from 663 Norwegian car drivers including both electric and conventional car drivers. The MANCOVA results showed that the most substantial differences in the measured constructs were between the sole electric car owners and the sole conventional car owners, whereas there were fewer differences between those who only own an electric car and those who own both an electric and a conventional car. Compared to the conventional car owners, electric car owners were younger and had a higher education and income level, and they reported more car use and higher level of knowledge about electric cars. In addition, electric car owners agreed with the positive attributes of electric cars more and reported higher level of personal norm, ascription of responsibility and awareness of consequences related to effects of car use to the environment. Finally, multinomial logistic regression results showed that attributes of electric cars were the strongest group of variables that increased probability of electric car ownership. Highlights: Owners of electric car, conventional car and both types of cars were compared. Owners of both cars had the highest level of knowledge score related to electric cars. Electric car owners reported the highest level of environmental and normative beliefs. Conventional car drivers rated the attributes of electric cars least positively. Instrumental attributes increased probability of electric car ownership most strongly.